Career choices in academia - Jürgen Janger; Klaus Nowotny (WWWforEurope, 2013)
Based on a unique survey, we conduct a stated choice experiment to examine the determinants of career choice in academia. Both early and later stage researchers value a balance between teaching and research, appropriate salaries, working with high-quality peers and good availability of external grants. Attractive academic jobs for early stage researchers feature in addition a combination of early independence and career (tenure) perspectives; later stage researchers favour jobs which make it easy to take up new lines of research, which pay according to a public scheme including a performance element and where research funding is provided by the university. Our findings have important implications for the structure of academic careers and for the organisational design of research universities. Furthermore, they shed light on the institutional determinants of the asymmetric mobility of highly talented scientists between the EU and the U. S.
Keywords: I23; I25; I28; 330; Academic careers; academic labour market; university organisation; brain drain